Lead Acetate Based Hybrid Perovskite Through Hot Casting for Planar Heterojunction Solar Cells - Shin, Gwang Su; Choi, Won-Gyu; Na, Sungjae; Gokdemir, Fatma Pinar; Moon, Taeho (KOREAN INST METALS MATERIALS, 2018)
Flawless coverage of a perovskite layer is essential in order to achieve realistic high-performance planar heterojunction solar cells. We present that high-quality perovskite layers can be efficiently formed by a novel hot casting route combined with MAI (CH3NH3I) and non-halide lead acetate (PbAc2) precursors under ambient atmosphere. Casting temperature is controlled to produce various perovskite microstructures and the resulted crystalline layers are found to be comprised of closely packed islands with a smooth surface structure. Lead acetate employed perovskite solar cells are fabricated using PEDOT:PSS and PCBM charge transporting layers, in p-i-n type planar architecture. Especially, the outstanding open-circuit voltage demonstrates the high crystallinity and dense coverage of the produced perovskite layers by this facile route. [GRAPHICS] .
Keywords: CH3NH3PbI3; Lead acetate; Hot casting; Air processing; Planar heterojunction solar cells; HIGHLY EFFICIENT; CRYSTAL-GROWTH; OPTOELECTRONIC QUALITY; HALIDE PEROVSKITES; DEPOSITION; CRYSTALLIZATION; PRECURSOR; FILM; PERFORMANCE; Materials Science